(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to delve into the nature of international financial reporting standards and the unified accounting system adopted in the Iraqi environment and financial ratios in the theoretical side. In the practical aspect, the results of some financial ratios of Basrah Gas Company were compared with the adoption of the financial statements prepared on the basis of the consolidated accounting system with the prepared financial statements Based on the International Financial Reporting Standards (IFRS). The research has reached a number of conclusions, including a difference in the accounting rules and practices between IFRS and the consolidated accounting system in force in Iraq. The adoption of IFRS has led to a decrease in profitability ratios and a positive impact on performance indicators compared with the financial ratios derived from the financial statements prepared on the basis of the consolidated accounting system. The main recommendations of the research were that analysts and users of financial statements should distinguish between changes in financial ratios and performance resulting from the transition to IFRS and business changes in financial analysis and decision-making.